Affinity-Tagged Miniprion Derivatives Spontaneously Adopt Protease-Resistant Conformations - Supattapone, Surachai (American Society for Microbiology, 2000)
An abridged PrP molecule of 106 amino acids designated PrP106 can form infectious miniprions in transgenic (Tg) mice (29). Addition of six-histidine (His(6)) affinity tags to selective sites within PrP106 resulted unexpectedly in new PrP proteins that spontaneously adopted protease-resistant conformations when expressed in neuroblastoma cells and Tg mice. Acquisition of protease resistance depended on the length, charge, and placement of the affinity tag. Introduction of the disease-linked mutation E200K into the sequence of PrP106(140/6His) increased the recovery of protease-resistant PrP fivefold, whereas introduction of the mutations C213A and Δ214–220 did not affect the recovery of protease-resistant PrP. Treatment of cultured cells expressing affinity-tagged PrP106 mutants with polypropyleneimine dendrimer rendered these proteins sensitive to protease digestion in a manner similar to wild-type PrP(Sc). We conclude that certain affinity-tagged PrP106 proteins spontaneously fold into conformations partially resembling, yet distinct from, wild-type PrP(Sc). These proteins might be useful tools in the identification of new disease-causing mutations as well as for screening compounds for therapeutic efficacy.